THE EFFECT OF USING RED BRICK WASTE MIXED WITH ASPHALT CONCRETE WEARING COURSE - DANANG ARIS MUNANDAR; SAHAT MARTUA SIHOMBING; LYDIA DARMIYANTI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Flexible pavement is a road construction that uses aggregate and asphalt as a binder to create a strong road layer. This pavement is able to withstand and distribute vehicle loads to the underlying soil layer and is often used on roads with reduced loads and traffic. This study used AC 60/70 penetration asphalt, which is suitable for hot climates and high traffic. With the large amount of red brick waste in Indonesia, this study utilizes the waste as a partial substitute for fine aggregate in the laston mixture. The title of this study is "The Effect of Using Brick Waste on Asphalt Concrete Wearing Course Mixture". The Marshall test characteristics on the AC-WC mixture using red brick powder as a filler substitute with a variation of 40% resulted in a stability value of 2487 kg, a VMA value of 36.51%, a flow value of 3.35 mm, a VIM value of 26.19% and an MQ value of 742 kg/mm ​​already meeting the specifications. For the VFB test value of 28.27%, it does not meet the 2018 Bina Marga specifications. Meanwhile, red brick powder with a variation of 80% produces a stability value of 2568 kg, a VMA value of 37.31%, a flow value of 3.4 mm, a VIM value of 27.12% and an MQ value of 756 kg/mm ​​already meets the specifications.